Prevalence and Factors Associated With Depression among School Going Adolescents in Bengaluru: A Cross-Sectional Study - Divya Udayakumar; Brunda NK; Lovely Livingston , Shruthi Shetty; Satya Kishore Chivukula (Indian Association of Preventive and Social Medicine, 2023)
Introduction:The period of adolescence involves a lot of emotional changes as it is a period of transition to adulthood demanding independence.Adolescents with depression are more likely to have anxiety, disruptive behavior disorder and substance abuse when compared to those who are not depressed. Objective: To estimate the prevalence of depression among school going adolescents.and to assess the factors associated with depression among them. Method: A cross-sectional study was conducted among school going adolescents aged 13-16 years in the urban field practice area of a Medical College. Depression was assessed using Beck's depression inventory (BDI). Total 896 adolescents were included in this study. Single stage cluster sampling method was done in which schools were considered as clusters and students constituted the sampling units. Schools were selected by simple random sampling technique using lottery method. Results: In this study about 45.2% of the adolescents had depressive disorder, out of which mild depression was reported among 22.2% students, 12.4% moderately depressed and 10.6% severe depression. Factors like mother's education, lack of communication by father and mother with their children, lack of needs satisfied by the fathers of the adolescents (61.9%), father's role in adolescents' life (62%) and domestic violence in family (69.7%) were some of the important reasons for developing depression among adolescents. Adolescent whose parents were having conflict (69.2%) were found be depressed when compared to those adolescents whose parents had no conflicts this difference was statistically significant (p<0.05). Conclusion: The prevalence of depression was found to be 45.2%. Finding of the study emphasizes the need for creating awareness about the early identification of behavioral changes leading to depression among adolescents by the parents and teachers. It is also important to emphasize to the parents on how their relationship and behavior towards the family affects the mental wellbeing of the adolescents.